Saxagliptin but Not Sitagliptin Inhibits CaMKII and PKC via DPP9 Inhibition in Cardiomyocytes - Koyani, Chintan N.; Trummer, Christopher; Shrestha, Niroj; Scheruebel, Susanne; Bourgeois, Benjamin; Plastira, Ioanna; Kickmaier, Sandra; Sourij, Harald; Rainer, Peter P.; Madl, Tobias; Sattler, Wolfgang; Pelzmann, Brigitte; et al. (Frontiers in Physiology, 2018)
Some oral anti-hyperglycemic drugs, including gliptins that inhibit dipeptidyl peptidase 4 (DPP4), have been linked to the increased risk of heart failure (HF) in type-2 diabetic patients. While the cardiovascular safety trial, TECOS, revealed no link between sitagliptin and the risk of HF, a substantial 27% increase in the hospitalization for HF was observed in type-2 diabetic patients treated with saxagliptin within the SAVOR-TIMI 53 trial. A previous in vitro study revealed that saxagliptin impairs the Ca2+/calmodulin-dependent protein kinase II (CaMKII)-phospholamban (PLB)-sarcoplasmic reticulum Ca2+-ATPase 2a axis and protein kinase C (PKC) activity in cardiomyocytes leading to impaired cardiac contractility and electrophysiological function. However, the link between saxagliptin and its target proteins (CaMKII and PKC) remains to be explored. Since DPP8 and DPP9 (but not DPP4) are expressed by cardiomyocytes and saxagliptin is internalized by cardiomyocytes, we investigated whether DPP8/9 contribute to saxagliptin-mediated inhibition of CaMKII and PKC activity. Structural analysis revealed that the DPP4-saxagliptin interaction motif (S630, Y547) for the cyanopyrrolidine group is conserved in DPP8 (S755, Y669) and DPP9 (S730, Y644). Conversely, F357 that facilitates binding of the anchor lock domain of sitagliptin in the S2 extensive subsite of DPP4 is not conserved in DPP8/9. In parallel, unlike saxagliptin, sitagliptin did not affect phosphorylation of CaMKII/PLB or activity of PKC in HL-1 cardiomyocytes. These findings were recapitulated by pharmacological inhibition (TC-E-5007, a DPP8/9 antagonist) and knock-down of DPP9 (but not DPP8). In primary mouse ventricular cardiomyocytes, saxagliptin (but not sitagliptin) impaired Ca2+ transient relaxation and prolonged action potential duration. These results suggest that saxagliptin-DPP9 interaction impairs the CaMKII-PLB and PKC signaling in cardiomyocytes. We reveal a novel and potential role of DPP9 in cardiac signaling. The interaction of saxagliptin with DPP9 may represent an underlying mechanism for the link between saxagliptin and HF. Elucidation of saxagliptin-DPP9 interaction and downstream events may foster a better understanding of the role of gliptins in cardiac signaling cascades.